Eco-friendly synthesis and characterization of Aloe vera/Gum Arabic/silver nanocomposites and their antibacterial, antibiofilm, and wound healing properties - Naveen, Kumar Vishven; Saravanakumar, Kandasamy; Sathiyaseelan, Anbazhagan; Wang, Myeong-Hyeon (Colloid and interface science communications, 2022)
Silver-nanoparticles are renowned for anti-bacterial properties but which carry toxicity-related concerns. Green-chemistry methods are promising to overcome these challenges. Hence, present work reports the eco-friendly fabrication, characterization, wound healing and bacteriostatic ability of Aloe vera-Gum Arabic‑silver-nanocomposite (Av-GA-Pc-AgNCs). The poly dispersion index (PDI) of 0.22 and zeta potential of −32.4 ± 6.2 mV were determined for Av-GA-Pc-AgNCs. FT-IR analysis evidenced the existence of functional moieties in Av-GA-Pc-AgNCs, related to bioorganic compounds of Aloe vera and Gum Arabic. Further, TEM analysis unveiled the spherical shape and particle size of Av-GA-Pc-AgNCs ranged from 28 to 38 nm. The Av-GA-Pc-AgNCs exhibited a strong antibacterial and anti-biofilm activity against B. cereus, and E. coli while remain non-toxic to NIH3T3 cells, chicken embryos and erythrocytes. The treatment of Av-GA-Pc-AgNCs resulted ~80% of wound healing activity. These results demonstrated that Av-GA-Pc-AgNCs were biocompatible, and have potential to remove biofilm and promote wound healing [Display omitted] •Aloe vera-gum Arabic‑silver nanocomposite (Av-GA-Pc-AgNCs) prepared and characterized.•Av-GA-Pc-AgNCs inhibited the growth and biofilm of B. cereus and E. coli.•Av-GA-Pc-AgNCs augmented the proliferation of NIH3T3 cells at lower concentrations.•Av-GA-Pc-AgNCs (500 μg/mL) demonstrated the biocompatibility to CAMs and erythrocytes.